Thomas & friends. Journey beyond Sodor [videorecording (DVD)] : the movie (Hit Entertainment, 2017)
Determined to prove his importance on Sodor, Thomas takes James' trucks and sets off on a big adventure to the Mainland. On the way, he makes friends with the cheerful and helpful 'Experimental Engines' but, after a wrong turn, finds himself lost in the steelworks. There, Thomas encounters two mysterious engines who instantly make him feel welcome but who aren't what they first seem.